The Relative Site Moisture Index: an Expansion of the Topographic Relative Moisture Index - Van de Grift, Jon (My University, 1996)
Soil moisture is an important factor influencing vegetation establishment and productivity. Several attempts have been made to develop an accurate means of characterizing soil moisture in the field without extensive monitoring. The Topographic Relative Moisture Index (TRMI), was developed as a tool for estimating relative soil moisture conditions in mountainous terrain using only slope characteristics. This study adds soil depth and soil texture parameters to the slope parameters of the TRMI, thereby creating the Relative Site Moisture Index (RSMI). This environmental scaler should be useful in non-mountainous environments, where the variability in slope characteristics is less than in regions of greater relief, to estimate relative soil moisture. These additional parameters should also increase the accuracy of the index in mountainous areas. Field measurements taken at Parfrey's Glen in southern Wisconsin are used to assess the accuracy of the RSMI. Analysis of the vegetation data collected indicate that the RSMI is a better predictor of soil moisture than the TRMI in this area.
Tables; Maps; Figures; Bibliography
Keywords: RSMI; TRMI; Topographic Relative Moisture Index; Relative Site Moisture Index